Differential levels of reactive oxygen species in murine preadipocyte 3T3-L1 cells cultured on type I collagen molecule-coated and gel-covered dishes exert opposite effects on NF-κB-mediated proliferation and migration. (2nd September 2018) - Liu, Xiaoling; Long, Xinyu; Liu, Weiwei; Yao, Guodong; Zhao, Yeli; Hayashi, Toshihiko; Hattori, Shunji; Fujisaki, Hitomi; Ogura, Takaaki; Tashiro, Shin-ichi; Onodera, Satoshi; Yamato, Masayuki; et al.
Abstract: Reactive oxygen species (ROS) participate in various cell responses in association with cell proliferation, migration, differentiation, and death. Extracellular matrix (ECM) serves as cellular microenvironments for many kinds of cells, affecting cell activities. However, whether or not ECM influences cellular ROS levels has not been well studied. In this study, cells are cultured on collagen I molecule-coated (mol. coated) dishes and collagen I fibrous gel-covered (gel) dishes to explore their influence on cell behaviours. We found that the levels of ROS in murine 3T3-L1 preadipocytes increased both in cells on mol. coated and those on the gel. Much higher ROS levels were found in the cells cultured on the gel. Cell proliferation and migration were stimulated to opposite directions between the cells on mol. coated and the cells on gel. ROS in a moderate level were positive regulators in the proliferation and migration of cells on mol. coated; however, ROS in a high level served as negative regulators in the cells on gel. These opposite effects on cell proliferation and migration affected by different ROS levels are in parallel with opposite levels of NF-κB p65 activation.